Notes exchanged between France and the United States on the subject of a multilateral treaty for the renunciation of war : together with the text of M. Briand's original proposal for a pact of perpetual friendship - Briand, Aristide, 1862-1932; Kellogg, Frank B. (Frank Billings), 1856-1937 (United States Government Printing Office, 1928)
Correspondance from December 28, 1927 through March 30, 1928 between French foreign minister Briand and United States Secretary of State Kellogg discussing a proposed multilateral treaty, which eventually became the General Treaty for Renunciation of War as an Instrument of National Policy.